2009
DOI: 10.1111/j.1365-2885.2008.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk secretion of nitrofurantoin, as a specific BCRP/ABCG2 substrate, in assaf sheep: modulation by isoflavones1

Abstract: Studies on residues in milk used for human consumption have increased due to health concerns and priority interest in the control of potentially risky drugs. The protein BCRP/ABCG2, present in the mammary epithelia, actively extrudes drugs into milk and can be modulated by isoflavones. Nitrofurantoin is a specific BCRP substrate which is actively excreted into milk by this transporter. In this research, we studied nitrofurantoin transport into milk in four experimental groups: G1-calves fed forage with isoflav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…Our results, in agreement with those previously published, showed a large difference in the concentration of nitrofurantoin into milk between wild-type and Bcrp1 −/− (9-fold higher in the wild-type mice), but we also observed a significant difference between wild-type animals with or without isoflavones, the excretion of NTF into milk being reduced two-fold. These results agree with our preliminary results obtained from lactating sheep (22,32), thus confirming that when a drug is a specific substrate of BCRP, milk secretion can be modulated by these isoflavones.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results, in agreement with those previously published, showed a large difference in the concentration of nitrofurantoin into milk between wild-type and Bcrp1 −/− (9-fold higher in the wild-type mice), but we also observed a significant difference between wild-type animals with or without isoflavones, the excretion of NTF into milk being reduced two-fold. These results agree with our preliminary results obtained from lactating sheep (22,32), thus confirming that when a drug is a specific substrate of BCRP, milk secretion can be modulated by these isoflavones.…”
Section: Discussionsupporting
confidence: 95%
“…A novel recent study on the effect of flavonoid chrysin on nitrofurantoin pharmacokinetics showed that this interaction occurs in rats but not in mice possibly due to the higher levels of BCRP in the small intestine in rats compared with mice (21). We obtained positive results regarding the role of exogenous isoflavones' administration in milk secretion of nitrofurantoin in ewes, but interindividual variation made the interpretation of results difficult (22).…”
Section: Introductionmentioning
confidence: 74%
“…Bcrp/BCRP is almost exclusively expressed on the apical surface of epithelial cells, including hepatocytes, proximal tubules, enterocytes, trophoblasts, yolk sac, and mammary glands as well as brain and retinal capillary endothelial cells (Table 8) (Maliepaard et al, 2001;Cooray et al, 2002;Jonker et al, 2002;Aronica et al, 2005;Tachikawa et al, 2005;Asashima et al, 2006;Fetsch et al, 2006;Pulido et al, 2006;Aleksunes et al, 2008b;Roberts et al, 2008). Expression of Bcrp/BCRP on lactating mammary glands in a number of species contributes to the excretion of chemicals into breast milk van Herwaarden et al, 2006Pérez et al, 2009).…”
Section: Klaassen and Aleksunesmentioning
confidence: 99%
“…Several studies have managed to increase the bioavailability and milk secretion of antibacterial agents, such as nitrofurantoin, or antitumorals, such as topotecan, or to improve brain penetration of the antitumoral imatinib with the use of ABCG2 and Pglycoprotein inhibitors, such as elacridar, the benzimidazole pantoprazole, or isoflavones (2,11,14,21,25). However, it has to be noted that the use of TCBZ for this purpose may be controversial in animals whose products are destined for human consumption or in areas of parasite endemicity due to the potential development of resistance.…”
Section: Discussionmentioning
confidence: 99%